Nursing care of newborns and infants with aortic coarctation in pre- and postoperative period - Skubiszewska, Agnieszka; Werner, Bożena (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Background. Aortic coarctation is narrowing of the aorta just below left subclavian artery. In the infantile type the obliteration occurs at the preductal position and untreated may result in early death from congestive heart failure. Aim. The aim of the study was to analyze nursing care of newborns and infants with coarctation of the aorta during perioperative period in the aspect of management and emerging nursing problems. Material and methods. Study group consisted of 10 children at the age ranging from 5 days to 8 months who undergone cardiosurgical repair for aortic coarctation. Medical documentation was analyzed with particular emphasis laid to postoperative nursing care charts. Results and conclusions. Before surgery absent femoral pulses were found in 8 children, systemic hypertension in 5, decrease of oxygen saturation in 4. Three patients required artificial ventilation and 2 had oliguria. Prostaglandin E1 was used in treatment of 5 newborns. In early postoperative period all patients required mechanical ventilation. After coarctation repair in 8 patients diuresis below 2,5 ml/kg/bw, in 6 hypertension and 4 decreased body temperature were observed. In children suffering from aortic coarctation blood pressure measurements should be performed on upper and on lower extremities in preoperative as well as in postoperative period. The main nursing problems in infants and newborns suffering from aortic coarctation are heart failure and systemic hypertension. Oliguria, systemic hypertension and decreased body temperature are common in children in early postoperative period.